2006
DOI: 10.21273/horttech.16.1.0039
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Availability from High-nitrogen-containing Organic Fertilizers

Abstract: Limited soil nitrogen (N) availability is a common problem in organic vegetable production that often necessitates in-season fertilization. The rate of net nitrogen mineralization (Nmin) from four organic fertilizers (seabird guano, hydrolyzed fish powder, feather meal, and blood meal) containing between 11.7% and 15.8% N was compared in a laboratory incubation. The fertilizers were mixed with soil from a field under organic management and incubated aerobically at constant moisture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
104
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(116 citation statements)
references
References 10 publications
9
104
1
2
Order By: Relevance
“…The three meals had an average N replacement value of 129 lb/acre; (equivalent to 86% of the N present in the meal at time of application) with no significant differences observed among the three seed meals in comparison to each other (individual means for N replacement value were: soybean, 76%; canola, 84%; mustard, 97%; pooled analysis CV = 35.6%). These rates are slightly greater than rates of N mineralization reported for feather meal, blood meal, or bird guano (on the order of 60% to 80% mineralization after 8 weeks) reported from lab studies (4,5). The values from the field study may be greater than those observed in the lab studies due to the longer period involved for mineralization to take place.…”
Section: Petiole Nitrate and Yield Datacontrasting
confidence: 54%
See 1 more Smart Citation
“…The three meals had an average N replacement value of 129 lb/acre; (equivalent to 86% of the N present in the meal at time of application) with no significant differences observed among the three seed meals in comparison to each other (individual means for N replacement value were: soybean, 76%; canola, 84%; mustard, 97%; pooled analysis CV = 35.6%). These rates are slightly greater than rates of N mineralization reported for feather meal, blood meal, or bird guano (on the order of 60% to 80% mineralization after 8 weeks) reported from lab studies (4,5). The values from the field study may be greater than those observed in the lab studies due to the longer period involved for mineralization to take place.…”
Section: Petiole Nitrate and Yield Datacontrasting
confidence: 54%
“…Compost is one potential source of N, however, it is variable depending on its source, and its effectiveness is limited by its relatively slow rate of mineralization (6,12). Work with high‐N containing organic fertilizers, such as blood and feather meal, has shown that these materials can release N in a timely manner for crop production (> 50% N mineralization within 8 weeks of application) (5). Research with teff ( Eragrostis tef ) has shown that mustard seed meal also has potential as an organic source of N (1).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, most perennial organic fruit production systems use strips of vegetation, such as legumes or cover crop mixes, in the alleys. In practice, the lack of economic justification for using cover crops when the land has a high value and when markets offer a price premium for organic vegetables may limit growers' use of cover crops as well as 4-year rotation systems Hartz and Johnstone 2006), despite that loss of long-term benefit may be observed.…”
Section: B Soil Healthmentioning
confidence: 99%
“…The C:N ratio of an amendment nutrient source is a robust indicator of potential N mineralization (Gale et al 2006), although mineralization and plant availability will vary according to soil incorporation or surface application, irrigation method used (Neilsen et al 2009), and soil health status. However, it can be considered that 47-60% of the organic N in blood meal, feather meal, guano, and fish powder is mineralized within 2 weeks, and up to 74% is mineralized after 8 weeks (Hartz and Johnstone 2006). For Tithonia diversifolia green manure, 50% of its N content is released within 1 week, and 80% of its N and P contents are released within 3 weeks (Gachengo et al 1998;Jama et al 2000;Ikerra et al 2006;Partey et al 2011).…”
Section: B Nutrient Budgetingmentioning
confidence: 99%
“…N is an especially limiting factor for crop growth on organic farms, because the organic N is not readily available to plants and needs to be transformed to dissolved inorganic forms (Gaskell and Smith 2007;Hartz and Johnstone 2006). In conventional farming, inorganic N is supplied by inorganic dissolved salts, which avoids the problem.…”
Section: Introductionmentioning
confidence: 99%